2014
DOI: 10.1016/j.jpsychires.2014.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of real world executive dysfunction in bipolar I disorder

Abstract: Background Bipolar disorder is characterized by impairments in cognitive functioning, both during acute mood episodes and periods of euthymia, which interfere with functioning. Cognitive functioning is typically assessed using laboratory-based tests, which may not capture how cognitive dysfunction is experienced in real-life settings. Little is known about the specific illness characteristics of bipolar disorder that contribute to cognitive dysfunction in everyday life. Methods Participants met DSM-IV criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
4
17
0
1
Order By: Relevance
“…Thus, cognitive flexibility training may be appropriate as a specific treatment target for individuals with childhood-onset BD throughout their entire childhood and adolescence, but such training may benefit individuals even if not started until young adulthood. Nevertheless, intervening earlier once a child is diagnosed with BD would be preferable, considering the well-studied links between reduced executive functioning and poor psychosocial outcomes in BD (Andreou and Bozikas, 2013; Buoli et al, 2014; Mora et al, 2013; Pavuluri et al, 2006a; Pavuluri et al, 2009; Peters et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cognitive flexibility training may be appropriate as a specific treatment target for individuals with childhood-onset BD throughout their entire childhood and adolescence, but such training may benefit individuals even if not started until young adulthood. Nevertheless, intervening earlier once a child is diagnosed with BD would be preferable, considering the well-studied links between reduced executive functioning and poor psychosocial outcomes in BD (Andreou and Bozikas, 2013; Buoli et al, 2014; Mora et al, 2013; Pavuluri et al, 2006a; Pavuluri et al, 2009; Peters et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in an fMRI meta-analysis, youths with BD showed more consistently decreased anterior cingulate activation during cognitive tasks than adults with BD (Wegbreit et al, 2014). These cognitive problems are important to study because many are associated with reduced psychosocial functioning and do not remit during euthymia (Andreou and Bozikas, 2013; Buoli et al, 2014; Mora et al, 2013; Pavuluri et al, 2006a; Pavuluri et al, 2009; Peters et al, 2014). Better knowledge of their pathophysiology could provide a cost-effective way to improve the lives of individuals with BD by spurring the development of novel pharmacological agents (Miskowiak et al, 2014) and cognitive remediation treatments (Dickstein et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively understudied are the contributions of cognitive functioning and sleep to sustained work disability, as both are often found to be impaired despite remission of mood symptoms and may in fact be inter-related (see Boland and Alloy, 2013 for a review of the theoretical relationship between sleep and neurocognition in BD). Numerous reports point to widespread cognitive deficits in the euthymic phase of BD, including deficits in verbal memory, verbal learning, attention, and executive functioning (Robinson et al, 2006; Torres et al, 2007; Arts et al, 2008, Bora et al, 2009; Kurtz et al, 2009; Mann-Wrobel et al, 2011; Peters et al, 2014). Studies including indices of work performance in their analyses have consistently reported associations between work disability and verbal learning and memory (Dickerson et al, 2004; Martinez-Ă€ran et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar spectrum disorders (BSDs) are characterized by periods of depression and/or mood elevation and are associated with impairment in many areas of functioning (Murray and Lopez, 1996; Peters et al, 2014). In addition, individuals with BSDs experience high rates of suicide (Angst et al, 2002), with previous reports indicating that 25 to 50% of individuals with bipolar I or II disorder have a lifetime history of a suicide attempt (Chen and Dilsaver, 1996; Leverich et al, 2003; Valtonen et al, 2005), twice the rate of individuals with unipolar depression (Chen and Dilsaver, 1996), and twenty to thirty times greater risk than the general population (Pompili et al, 2013).…”
Section: Introductionmentioning
confidence: 99%